Pengaruh Penggunaan Media Gambar Terhadap Motivasi Belajar Pendidikan Agama Kristen dan Budi Pekerti Kelas VIII Semester Genap SMP N 2 Sipoholon Tahun Pembelajaran 2022/2023 (Jurnal Pendidikan Agama dan Teologi, 2023)
Abstract: The aim of this research is to determine the positive and significant influence of the use of image media on learning motivation for Christian Religious Education and Character Education for Class VIII, even semester of SMP N 2 Sipoholon, Academic Year 2022/2023. The method used in this research is descriptive quantitative. The population is all students in class VIII, Even Semester, SMP N 2 Sipoholon for the 2022/2023 academic year, totaling 109 people and a sample of 38 people was determined, namely 35% of the total population. Data was collected using a positive closed questionnaire totaling 46 items, of which 23 questionnaire items were for variable even at SMP N 2 Sipoholon 2022/2023 Academic Year: 1) Test the analysis requirements: a) test a positive relationship, obtained a value of rxy = 0.511 > rtable(a=0.05,n=38) = 0.320, thus it is known that there is a relationship positive relationship between variable 2) Influence test: a) Regression equation test, obtained regression equation Y=33.80+0.52X. b) Regression coefficient of determination test (r2) = 26.2%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(a=0.05, dk numerator k=22, dk denominator=n-2=38-2=36) namely 12.74 > 1.51 Thus Ha accepted and H0 rejected.